PENILAIAN SARANA DAN PRASARANA LINGKUNGAN PERUMAHAN SEHAT BERDASARKAN ASPEK PERATURAN PEMERINTAH - Misnawati; Norminawati Dewi; Retna Hapsari Kartadipura; Chudori Sahlan (Jurnal Rekayasa Konstruksi, 2022)
A healthy home is one of the basic human needs which is an important factor in increasing human dignity, so it is necessary to create conditions that can encourage the development of healthy housing. The results of observations in the field can be concluded whether or not the requirements of a housing, in this case the Ketapang Asri Complex, are met or not. Health requirements (not located in a former landfill, air quality, drainage facilities, playground, clean water. Based on regulation of No. 829/MENKES/SK/VII/1999 Ketapang Asri Complex only around 80% of these requirements because there is a shortage in air quality, playgrounds, and garbage disposal while the location and greening requirements have met these requirements.